THE CORRELATION BETWEEN THE VOCABULARY MASTERY AND THE SPEAKING ABILITY IN DESCRIBING PEOPLE BY THE SECOND YEAR STUDENTS OF SMPN 12 BINTAN - Aristi, Nina; Prawati, Atni; Maria, Desri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The objective of this research is to find out the correlation between vocabulary mastery and speaking ability in describing people by the second year students of SMPN 12 Bintan. The sample of this research was class VIII 2, which consist of 30 students. The data were collected by using two kinds of test, vocabulary test and speaking test. The result of this research showed that the second year students of SMPN 12 Bintan got good to excellent level with the average score 83.16 in vocabulary test and in speaking the students got good level with average to good score 73.56 The result of this research proved that there is a positive correlation between vocabulary mastery and speaking ability in describing people. The rxy distribution of the coefficient correlation is 0.68. It means that the correlation was in moderate level. So, Ha (alternative hypothesis) of this research is accepted and null hypothesis (Ho) is rejected. There was no much different between the students’ vocabulary score and student’ speaking score. In other words, it can be concluded that students who are good in vocabulary will also tend to be good in speaking.Keywords: correlation, vocabulary mastery, speaking ability